Community Information Group Empowerment by the Office of Communication and Informatics in an Effort to Encourage Information Dissemination - Irianto, Winno Riskinda (The Commercium, 2023)
Indonesia’s vast geographic location will cause an information gap, including in Mojokerto Regency. To overcome the information gap, the government formed a group engaged in the information sector so that information dissemination can be achieved. This group is called the Community Information Group or KIM. With the formation of KIM, empowerment needs to be carried out by the local government, especially the Mojokerto District Communication and Information Service so that KIM can run according to its duties. The purpose of this research is to find out how the KIM empowerment by the Mojokerto District Communication and Information Service is in an effort to encourage information dissemination. This study uses Wrihatnolo and Dwidjowijoto’s Empowerment Theory which explains that empowerment includes 3 stages namely, the awareness stage, the capacity building stage and the empowerment stage. The results showed that the Mojokerto District Communication and Information Service carried out 3 stages of empowerment in accordance with the theory, namely first awareness raising, the Mojokerto Regency Diskominfo carried out "ledhang" or socialization in every sub-district in Mojokerto Regency. The second is capacity building, Mojokerto Regency Diskominfo provides capacity through seminars, technical guidance and also workshops for KIM. The third is empowerment, the Mojkoerto Regency Diskominfo gives trust to KIM to process media independently. Keywords: Empowerment, Community Information Group, Information Dissemination